The Valuation of Google IPO: An Application of Real Options Theory - Ning, Da (2007)
Company valuation is always the most complex part in initial public offering (IPO). For decades, traditional valuation models such as discounted cash flow (DCF) have been widely applied in pricing IPO. However, recently, a lot of criticisms have been raised on these methods and, at the same time, real options approach are gradually being accepted by more and more managers. This paper presents a model which applies real-option theory solving the problem of Google IPO valuation. The model is developed base on Schwartz and Moon (2001)s model, using estimated parameters and worked out by Monte Carlo simulations. Through comparison with real stock performance between Aug. 2004 and Aug. 2005, it shows that the model provides a fairly accurate valuation result of Google IPO in 2004. In the result analysis part, sensitivity analysis has been adopted to test each variables influence to the model and found out that the stochastic variables including revenues and long-term variable costs have significant influence on the model. The finding shows that although this model can provide an accurate IPO valuation, it can only be adopted in the companies with high growth rate of revenues. If this limitation can not be solved, this model can not be widely applied in the future.